2013
DOI: 10.1007/s00595-013-0659-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum total bilirubin elevation is a predictor of the clinicopathological severity of acute appendicitis

Abstract: In patients with an elevated preoperative STB level, it is very likely that the inflammation is severe and that the disease has progressed to a severe condition histopathologically; therefore, meticulous attention should be paid to the selection of the surgical procedure, as well as to the postoperative clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Elevated CRP, as a sensitive marker of systemic inflammatory response, was associated with poor prognosis of many cancers [25][26][27]. It had been reported that elevated preoperative serum total bilirubin level was associated with severe inflammation and could reflect the severity of acute appendicitis and poor outcomes of biliary tract cancers [28,29]. Therefore, the results of our study indicated that preoperative CRP and total bilirubin levels are very useful for predicting survival in patients with GBC.…”
Section: Discussionmentioning
confidence: 52%
“…Elevated CRP, as a sensitive marker of systemic inflammatory response, was associated with poor prognosis of many cancers [25][26][27]. It had been reported that elevated preoperative serum total bilirubin level was associated with severe inflammation and could reflect the severity of acute appendicitis and poor outcomes of biliary tract cancers [28,29]. Therefore, the results of our study indicated that preoperative CRP and total bilirubin levels are very useful for predicting survival in patients with GBC.…”
Section: Discussionmentioning
confidence: 52%
“…Although the comparisons of CRP, and total bilirubin levels between negative and positive appendectomy cases did not reveal statistical significance (p > 0.05), these parameters were significantly higher in the gangrenous/perforated appendicitis group than the other two groups of patients (p < 0.01, and p < 0.01, respectively Despite numerous studies evaluating the predictive role of total bilirubin levels for acute appendicitis cases [19][20][21][22][23][24][25], no studies investigating the significance of direct and indirect bilirubin levels for this subject have been detected in the literature so far. The assessment of direct bilirubin levels, which is considered to represent the novelty of our study, revealed significantly elevated values in patients with either acute non-complicated, or gangrenous/perforated appendicitis (p < 0.01).…”
Section: Discussionmentioning
confidence: 93%
“…In another study, Vaziri et al stated that the mean bilirubin levels were significantly higher for patients with perforated acute appendicitis (p < 0.01) [12]. According to the series of Nomura et al, which evaluated data from 410 appendectomized patients, elevated serum total bilirubin levels increased the risk of gangrenous appendicitis approximately two folds (p < 0.01, OR 1.79) [22]. In our study, the odds ratio for elevated total bilirubin levels was calculated to be 4.7 referring to an approximately five fold likelihood for appendiceal gangrene/perforation (p < 0.05, OR: 4.70).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have emerged to show that serum bilirubin levels could indicate patients with acute appendicitis (23). Some studies have also formulated that hyperbilirubinemia can be associated with perforation and severity of the appendicitis (3, 18, 2427). Elevated serum bilirubin levels can be explained by the invasion of the Gram-negative bacteria to the appendix, leading to direct invasion or translocation of the germs in the portal system and the liver, interfering with bilirubin excretion through bile ducts by endotoxin action.…”
Section: Introductionmentioning
confidence: 99%